Interpreting the Critique of Pure Reason in Argentina: The Beginnings of Kantian Philosophy at the University of Buenos Aires - Pelegrin, Laura Alejandra (2025)
Abstract. The research explores the origins of Kantian philosophy at the University of Buenos Aires by focusing on the work of Mario Caimi. Although shifts in Caimi’s emphases and perspectives can be traced over time, this study argues that a consistent orientation underlies his research: the problem of method as the guiding thread of Kant’s philosophy. This interpretative line, inaugurated by Caimi, has decisively shaped the development of Kantian studies at the University of Buenos Aires, establishing a distinctive hermeneutic framework that has since been taken up and further developed by members of the Kant Research Group in Buenos Aires. Through an analysis of key moments in Caimi’s reading of Kant – ranging from the Transcendental Aesthetic to the Transcendental Dialectic – this study aims to demonstrate how the focus on philosophical method reveals a coherent interpretative strategy. It also highlights two defining features of Caimi’s exegesis: the rejection of psychologistic interpretations of Kant, and the insistence on the centrality of sensibility, particularly with respect to the role of sensation.